Toward Muzakki Inner Peace: A Semantic Analysis of Sakan in the Qur’anic Discourse on Zakat - Abdur Rofiq; M Fahmi Hidayat (RUSYDIAH: Jurnal Pemikiran Islam, 2026)
This study examines the concept of sakan in the Qur’anic discourse on zakat and formulates it as a framework for understanding the inner transformation of the muzakki. Existing zakat studies tend to emphasize legal compliance, institutional trust, distribution, and zakat recipient (mustahiq) welfare, while the inward condition of the zakat zakat giver (Muzakki) remains less explored. Using a qualitative conceptual method, this study combines Qur’anic semantic analysis, classical tafsir, Fazlur Rahman’s hermeneutic reconstruction, and Kuntowijoyo’s paradigm of Islam as science. The semantic analysis shows that the root sakan is associated with stability, settledness, and the calming of disturbance. Classical tafsir on Surah al-Tawbah 9:103 interprets sakan through six interrelated meanings: nearness to God (qurb), divine mercy (rahmah), dignity or composure (waqar), steadfastness (thabat), security (amn), and tranquility (tuma'ninah). Through hermeneutic reconstruction, the verse is understood as presenting zakat as a process of purification, spiritual growth, and inward reassurance. This study proposes Muzakki Inner Peace as a Qur’anically grounded concept that describes the spiritual and psychological stabilization of the Zakat giver. The concept broadens zakat studies by positioning the inner transformation of the muzakk? alongside the social and distributive functions of zakat.